2015
DOI: 10.3233/bme-151465
|View full text |Cite
|
Sign up to set email alerts
|

Variation of patient imaging doses with scanning parameters for linac-integrated kilovoltage cone beam CT

Abstract: Abstract. To evaluate the Elekta kilovoltage CBCT doses and the associated technical protocols with patient dosimetry estimation. Image guidance technique with cone-beam CT (CBCT) in radiation oncology on a daily basis can deliver a significant dose to the patient. To evaluate the patient dose from LINAC-integrated kV cone beam CT imaging in imageguided radiotherapy. CT dose index (CTDI) were measured with PTW TM30009 CT ion chamber in air, in head phantom and body phantom, respectively; with different combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Although the effective dose does not represent the exposure of an individual patient, it is useful for comparing doses from different examinations 16 . Consequently, Liao et al measured CTDI w in CBCT and calculated DLP from the CTDI w 17 . Moreover, Abuhaimed et al reported that DLP is useful for comparing patient doses between diagnostic CT and CBCT in radiation therapy 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effective dose does not represent the exposure of an individual patient, it is useful for comparing doses from different examinations 16 . Consequently, Liao et al measured CTDI w in CBCT and calculated DLP from the CTDI w 17 . Moreover, Abuhaimed et al reported that DLP is useful for comparing patient doses between diagnostic CT and CBCT in radiation therapy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Consequently, Liao et al measured CTDI w in CBCT and calculated DLP from the CTDI w . 17 Moreover, Abuhaimed et al reported that DLP is useful for comparing patient doses between diagnostic CT and CBCT in radiation therapy. 18 This study calculated DLP by multiplying the CTDI w by the x-ray beam width in a longitudinal direction.…”
Section: Discussionmentioning
confidence: 99%